ANALISIS DAMPAK KRISIS EKONOMI TERHADAP PERKEMBANGAN WILAYAH KABUPATEN BEKASI - Nandang Najmulmunir (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2002)
Economical crisis in 1997 have impacted to the local economy, especially for Bekasi County. In 1986, Bekasi had three economical based sectors, and in 1999 only one economical based sector. In the period of 1996 - 1999 the regional economy grew significantly almost for all secto. The sector of industry had dominated the Gross Domestic Regional Product and the economic growth hade produced inequity among sub county (kecamatan), especially for the income per capita indicator.